Determinants of Dividend Policy of South Korean Listed Firms - Dr. Arindam Banerjee (Asian Journal of Finance & Accounting, 2024)
Ever since publication of the seminal works of John Lintner (1956) and Miller and Modigliani (1961), dividend policy continues to be a significantly debated research topic. Among the many unanswered questions, doubt remains on the specific reasons that determine dividend policy and whether it can be structured either in a dependent or independent manner. This study aims to investigate the factors of dividend payout policy on firms listed on South Korean stock exchange (KRX). The study involves 5 distinct variables that are considered as possible causes of dividend payout policy. The study includes development of 5 research hypothesis that are used to represent the primary theories of corporate dividend payouts. Fixed-effect regression model is applied on a sample of 30 companies listed on South Korean stock exchange over a period of 4 years spanning from 2014 to 2017. The specific model was chosen to test the relationship between determinants of dividend payout policy and its subsequent impact on the same. The study expects to potentially increase domain knowledge in the research area of dividend policy with a strong notion to improve prediction as well as establish a relationship between factors that determine dividend policy and its subsequent impact on the same on South Korean firms.